Unveiling the Complex Characters in The Glass Menagerie: A Psychological Analysis of Intriguing Personalities - Zulkarnain, Zulkarnain; Kurniawan, Redite; Widiati, Bidarita; Fachrurrozi, Fachrurrozi (JOLLT Journal of Languages and Language Teaching, 2024)
Literature serves as a reflective medium that captures and articulates the intricacies of social reality, providing a profound portrayal of real-life phenomena. It functions as a vital record, encapsulating the observations and perceptions of individuals in their lived experiences. In essence, literature is an eloquent description of life itself. This study specifically delves into the exploration of personalities within the context of the play "The Glass Menagerie" by Tennessee Williams, elucidating the significance of the characters' actions. To achieve a nuanced understanding, this research adopts personality theories to delineate the distinctive traits of the main characters and draws upon psychological and motivational theories to discern the underlying meanings of their actions. Employing a qualitative descriptive method with content analysis, the study aims to fulfill its research objectives, namely, providing detailed characterizations of Amanda, Tom, and Laura Wingfield, and unraveling the meanings and implied messages conveyed through their actions. The analytical process involves the systematic collection, scrutiny, and interpretation of data, culminating in well-grounded conclusions. The findings of this research shed light on various personalities, actions, and the implicit messages embedded in the conduct of the main characters, namely Laura, Tom, and Amanda Wingfield. Notably, the study identifies Laura as a character predominantly influenced by her Id, while Tom and Amanda are portrayed as personalities shaped by their Egos. The outcomes of this investigation contribute valuable insights that can inform the implementation of drama-based learning. By engaging with and appreciating literary works, students stand to enhance not only their language proficiency but also cultivate a sense of comfort and familiarity with the nuanced complexities of human behavior and interpersonal dynamics.